2022
DOI: 10.1111/ppa.13687
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of fig cultivars to Diaporthe canker in Iran

Abstract: Edible fig (Ficus carica, family Moraceae) is probably native to southwest Asia, with Iran, one of the world's top fig-producing countries, behind Turkey, Morocco, Greece and Spain, with 107,791 tonnes of fig production annually (FAO, 2020). Fars Province, in southern Iran, has appropriate conditions for growing organic dried figs. The province is Iran's leading dried fig producer and 51,000 ha are devoted to fig cultivation in its arid and semi-arid regions (Jafari et al., 2018). The dominant commercial organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies have documented similar drought stress effects on plants inoculated with Cytospora species ( Guyon et al., 1996 ; Kepley and Jacobi, 2000 ; McIntyre et al., 1996 ). Bolboli et al. (2022) reported variation in the susceptibility of different edible fig cultivars ( Ficus carica ) to Diaporthe cinerascens with drought-tolerant cultivars being reported as non-susceptible to fig canker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have documented similar drought stress effects on plants inoculated with Cytospora species ( Guyon et al., 1996 ; Kepley and Jacobi, 2000 ; McIntyre et al., 1996 ). Bolboli et al. (2022) reported variation in the susceptibility of different edible fig cultivars ( Ficus carica ) to Diaporthe cinerascens with drought-tolerant cultivars being reported as non-susceptible to fig canker.…”
Section: Discussionmentioning
confidence: 99%
“…infections occurs and that some cultivars may be less susceptible or not susceptible to Cytospora canker. Within the edible fig production system ( Ficus carica ), fig canker ( Diaporthe cinerascens ) is a major limiting factor; researchers recently reported a drought-tolerant fig tree cultivar to be non-susceptible to the canker pathogen ( Bolboli et al., 2022 ). Thus, the objectives of this study were to evaluate thirteen peach cultivars, commonly planted in western Colorado, for susceptibility to C. plurivora D.P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms include lesions on the trunk and branches, death of bark and woody tissues, limb dieback, leaf yellowing, defoliation and consequently, death of the fig trees (Figure 1). In December 2020, a field survey was performed to investigate the diversity and pathogenicity of ascomycete fungi associated with canker and dieback symptoms on fig trees in Mazandaran province, northern Iran (Bolboli et al., 2022a; Bolboli et al., 2022b). As part of this survey, two unknown isolates were recovered from one fig tree.…”
Section: Figurementioning
confidence: 99%
“…In recent years, various cereal fields in Fars Province of Iran have been surveyed to isolate and identify Pythium s.l. species [43,45,46]. These studies revealed rice paddies are a favorable ecological niche for Pythium s.l.…”
Section: Introductionmentioning
confidence: 99%